Using Underwater Pulse Oximetry in Freediving to Extreme Depths to Study Risk of Hypoxic Blackout and Diving Response Phases - Mulder, Eric; Sieber, Arne; Schagatay, Erika (Frontiers in Physiology, 2021)
Deep freediving exposes humans to hypoxia and dramatic changes in pressure. The effect of depth on gas exchange may enhance risk of hypoxic blackout (BO) during the last part of the ascent. Our aim was to investigate arterial oxygen saturation (SpO2) and heart rate (HR) in shallow and deep freedives, central variables, which have rarely been studied underwater in deep freediving. Four male elite competitive freedivers volunteered to wear a newly developed underwater pulse oximeter for continuous monitoring of SpO2 and HR during self-initiated training in the sea. Two probes were placed on the temples, connected to a recording unit on the back of the freediver. Divers performed one “shallow” and one “deep” constant weight dive with fins. Plethysmograms were recorded at 30 Hz, and SpO2 and HR were extracted. Mean ± SD depth of shallow dives was 19 ± 3 m, and 73 ± 12 m for deep dives. Duration was 82 ± 36 s in shallow and 150 ± 27 s in deep dives. All divers desaturated more during deeper dives (nadir 55 ± 10%) compared to shallow dives (nadir 80 ± 22%) with a lowest SpO2 of 44% in one deep dive. HR showed a “diving response,” with similar lowest HR of 42 bpm in shallow and deep dives; the lowest value (28 bpm) was observed in one shallow dive. HR increased before dives, followed by a decline, and upon resurfacing a peak after which HR normalized. During deep dives, HR was influenced by the level of exertion across different diving phases; after an initial drop, a second HR decline occurred during the passive “free fall” phase. The underwater pulse oximeter allowed successful SpO2 and HR monitoring in freedives to 82 m depth – deeper than ever recorded before. Divers’ enhanced desaturation during deep dives was likely related to increased exertion and extended duration, but the rapid extreme desaturation to below 50% near surfacing could result from the diminishing pressure, in line with the hypothesis that risk of hypoxic BO may increase during ascent. Recordings also indicated that the diving response is not powerful enough to fully override the exercise-induced tachycardia during active swimming. Pulse oximetry monitoring of essential variables underwater may be an important step to increase freediving safety.